Optimasi Sudut Terminal Rudal Menggunakan Simulasi Monte Carlo Probabilistik - Shilfa Nisa Agustin; Y. H. Yogaswara; Robertus Heru Thirarjanto; Larasmoyo Nugroho (Fakultas Teknik Universitas Garut, 2026)
Modern missiles, loitering munitions, and glide bombs are increasingly utilized due to their high-precision strike capabilities. However, in urban and complex environments where targets are often hidden behind obstacles, these systems frequently fail to achieve optimal terminal impact angles. This study addresses the limitations of conventional GPS/INS systems by optimizing the terminal angle using a numerical statistical approach based on Monte Carlo simulation. The simulation was conducted on an online cloud platform with 10,000 iterations to handle operational uncertainties. The results demonstrated a reduction in vertical angle error of up to 31.6%, an increase in altitude error of 10.7%, and an increase in hit probability to 84.8% compared to conventional methods. This approach enables missiles to achieve a more effective balance between penetration capability and impact accuracy, which is critical in contested and cluttered battlefields. This study concludes that integrating Monte Carlo simulation provides a more robust solution for improving attack effectiveness in complex environments. Future research is recommended to include hardware-in-the-loop testing and artificial intelligence integration.